2023
DOI: 10.3847/2041-8213/ad0158
|View full text |Cite
|
Sign up to set email alerts
|

JWST CEERS and JADES Active Galaxies at z = 4–7 Violate the Local M –M Relation at >3σ: Implications for Low-mass Black Holes and Seeding Models

Fabio Pacucci,
Bao Nguyen,
Stefano Carniani
et al.

Abstract: JWST is revolutionizing our understanding of the high-z Universe by expanding the black hole horizon, looking farther and to smaller masses, and revealing the stellar light of their hosts. By examining JWST galaxies at z = 4–7 that host Hα-detected black holes, we investigate (i) the high-z M •–M ⋆ relation and (ii) the black hole mass distribution, especially in its low-mass range (M • ≲ 106.5 M ⊙). Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 58 publications
8
33
0
Order By: Relevance
“…5 The JWST UV LF is systematically higher than that measured at z ∼ 7 with the SHELLQs survey (Matsuoka et al 2023). At least 23 of the candidate AGN thus far have reported spectroscopic confirmations with NIRSpec (Pacucci et al 2023). However, classical diagnostics alone have been deemed insufficient to confirm secure AGN detections since the NIRSpec resolutions are borderline (R ∼ 300 compared to the required R ∼ 500), which could also contribute to the source of the discrepancy (Übler et al 2023).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…5 The JWST UV LF is systematically higher than that measured at z ∼ 7 with the SHELLQs survey (Matsuoka et al 2023). At least 23 of the candidate AGN thus far have reported spectroscopic confirmations with NIRSpec (Pacucci et al 2023). However, classical diagnostics alone have been deemed insufficient to confirm secure AGN detections since the NIRSpec resolutions are borderline (R ∼ 300 compared to the required R ∼ 500), which could also contribute to the source of the discrepancy (Übler et al 2023).…”
Section: Discussionmentioning
confidence: 89%
“…AGN at z ∼ 4-7 identified in JWST and previous literature have bolometric luminosities covering a wide range and inferred black hole masses of 10 6 -10 9 M e . Many of the derived black hole to stellar mass ratios are about 10 to 100 times greater than expected from the local population (e.g., Pacucci et al 2023;Stone et al 2023;Yue et al 2023), with one candidate black hole (Bogdan et al 2023) also showing evidence for being as massive as the stellar host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a route to test the paradigm of AGN feedback quenching at early epochs, using photometric imaging data from JWST-CEERS, in addition to comparisons at lower redshifts with HST-CANDELS and SDSS. Interestingly, recent papers have found that dynamically measured black hole mass does not correlate strongly with stellar mass in the early Universe, but is still closely connected to central velocity dispersion, and hence, the galaxy potential (see Maiolino et al 2023;Pacucci et al 2023).…”
Section: Agn Quenching In the Early Universementioning
confidence: 99%
“…Additionally, about 25 galactic systems hosting a central SMBH have been spectroscopically detected by JWST in the redshift range 4  z  10, typically using the broad emission line scaling relations (e.g., Maiolino et al 2023a;Übler et al 2023;Furtak et al 2023;Goulding et al 2023;Harikane et al 2023;Kocevski et al 2023). Recently, Pacucci et al (2023) and Maiolino et al (2023a) argued that these systems violate the local M • − M å relation (Kormendy & Ho 2013;Reines & Volonteri 2015) at >3σ. Moreover, Bogdan et al (2023) and Natarajan et al (2023) reported the X-ray detection of an SMBH at z = 10.3, with a mass comparable to the stellar mass of its host, and found that the photometric properties of two galaxy candidates at z ∼ 13 could be explained by an accreting SMBH of ∼10 8 M e .…”
Section: Introductionmentioning
confidence: 99%